2017
DOI: 10.1016/j.compstruct.2017.08.085
|View full text |Cite
|
Sign up to set email alerts
|

Thermal buckling analysis of cylindrical shell with functionally graded material coating

Abstract: Abstract:The shell with functionally graded material (FGM) coating is a novel high temperature resistant structure, which has been increasingly applied in the aerospace, nuclear, turbo machinery and other engineering fields. However, there are some defects for practical structure due to the limitation of manufacturing technique. But relevant theoretical research on the thermal buckling behavior of the imperfect cylindrical shell is rather limited in most open literature. Therefore, this work proposed to establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The study highlighted the potential of FGM in mitigating stress singularities along the interfaces. Based on the Fourier series expansion method, Han et al [20] conducted a comprehensive investigation on the buckling behavior of a cylindrical shell coated with FGM under thermal loading conditions. Mao et al [21] simulated the sliding interaction between an FGM-coated half-plane and a homogeneous half-plane to investigate the frictional heat and thermal contact resistance in brake systems.…”
Section: Introductionmentioning
confidence: 99%
“…The study highlighted the potential of FGM in mitigating stress singularities along the interfaces. Based on the Fourier series expansion method, Han et al [20] conducted a comprehensive investigation on the buckling behavior of a cylindrical shell coated with FGM under thermal loading conditions. Mao et al [21] simulated the sliding interaction between an FGM-coated half-plane and a homogeneous half-plane to investigate the frictional heat and thermal contact resistance in brake systems.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that the buckling behaviour of these structures under thermal loading is different from that under mechanical loading, and the buckling load is affected by the material properties and boundary conditions. Han [14] derived the buckling load and critical buckling mode of the cylindrical shell and showed that the buckling load of the cylindrical shell under thermal loads was lower than that under mechanical loads. Kadoli and Ganesan [15] considered a rectangular tube and a cylindrical shell made of aluminium alloy and subjected them to thermal loads and showed that the buckling behaviour of the structures was significantly affected by the thermal load.…”
Section: Introductionmentioning
confidence: 99%
“…Using Von-Karman-Donnell theory, thermal buckling (Daikh, 2020) and post-buckling (Hieu and Tung, 2020) studies on FG sandwich cylindrical shell was performed, the analysis reveals the effect of skin thickness and its volume composition, which played a predominant role in increasing the buckling load. The thermal buckling of FG coated cylindrical shell was found to be increased as the coating thickness increases (Han et al , 2017). Al-Furjan et al (2020) performed buckling and post-buckling analysis on a disk by using von Karman’s non-linear plate theory.…”
Section: Introductionmentioning
confidence: 99%